1989
DOI: 10.1111/j.1365-2044.1989.tb09263.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between propofol and thiopentone as induction agents in obstetric anaesthesia

Abstract: SummaryTwo comparable series of 21 patients who had elective Caesarean section had general anaesthesia induced by thiopentone sodium 4.53 (SD 0.65) mglkg or propofol2.15 (SD 0.26) mglkg. Maintenance was similar for both groups. Blood pressure was lower in the propofol group during the induction-delivery interval. Umbilicallmaternal vein ratios for thiopentone and propofol were 8.5 and 7.2 respectively. Infant wellbeing as judged by Apgar score and cord blood analysis showed little difference between the two in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
2

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 13 publications
1
14
1
2
Order By: Relevance
“…There have been several studies comparing propofol to thiopental for induction of anaesthesia for elective Caesarean section [20][21][22][23][24][25][26][27][28][29][30]. These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies comparing propofol to thiopental for induction of anaesthesia for elective Caesarean section [20][21][22][23][24][25][26][27][28][29][30]. These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies [21,22] observed signs of lighter anaesthesia in the propofol group; however out of 516 women randomly allocated to propofol or thiopental [20][21][22][23][24][25][26][27][28][29][30] there were two episodes of recall, both occurring with thiopental [20,27]. Three studies [24,27,29] suggested an improved maternal recovery with propofol while four [20][21][22]30] found no difference. Overall, the literature suggests that propofol appears to be a valid, but not an obviously superior, choice to thiopental for elective Caesarean section.…”
Section: Resultsmentioning
confidence: 99%
“…[37][38][39][40] The elevation in urinary PBG postoperatively may raise some concern about the safety of propofol in patients with porphyria. However, there were no clinical manifestations of acute porphyria and PBG levels in this asymptomatic patient were extremely elevated well before surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Se usado em infusão contínua, parece sofrer metabolismo ou captação contínua pelos tecidos fetais 29 , e essa não parece ser uma boa técnica para anestesia obstétrica, embora não seja grande a redução nos índices de capacidade neurológica e adaptativa do recém-nascido 30 . Em comparação com o tiopental, esse hipnótico apresenta resultados contraditórios com relação aos índices de recuperação do recém-nascido [31][32][33] . Tem a vantagem de reduzir a resposta hipertensiva à intubação traqueal 30,32 , mas já foi demonstrado que ele relaxa a musculatura uterina humana isolada 34 .…”
Section: Drogas Anestésicas E Efeitos Fetaisunclassified
“…Em comparação com o tiopental, esse hipnótico apresenta resultados contraditórios com relação aos índices de recuperação do recém-nascido [31][32][33] . Tem a vantagem de reduzir a resposta hipertensiva à intubação traqueal 30,32 , mas já foi demonstrado que ele relaxa a musculatura uterina humana isolada 34 . No todo, não parece vantajoso como indutor rotineiro da anestesia para cesarianas 2 .…”
Section: Drogas Anestésicas E Efeitos Fetaisunclassified